Democratisation, Civil Society, and the Future of Acheh - Thaib, Lukman (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
One noteworthy future of the recent landmark changes in Indonesian politics is the collapse of the Soeharto government in the name of democracy, which was followed by a wider crisis of the Indonesian nation-state. One aspect of this crisis is the strengthening of the secessionist movement of Acheh (Sumatra) calling into question the country’s national boundaries, very much a legacy of the Dutch colonial era. It is intended here to examine first the current crisis of the Indonesian nation-state by focusing on how Indonesia nationalism emerged and how Indonesia as a nation-state was formed as well as the process by which Acheh became a part of that republic. This will be followed by the question of whether the current process of democratisation in Indonesia will strengthen its national unity and prevent Acheh from seceding. In other words, will Acheh achieve its independence from Indonesia as Indonesia takes the road towards deepening democratisation? The role of the Achehnese NOGs in the dissemination of democratic ideas and the coalition between civil societies and political parties in addressing the Acheh question will also be evaluated. Another extremely important point which needs to be looked at is the obstacles to the peace process in Acheh.